Biodegradation of Polychlorinated Biphenyls Using Acclimadzed Biofilmina Three-Phase Fluidized Bed Aerobic Reactor - Joseph Auresenia; Donna Marie G. Taleon (Department of Chemical Engineering, Universitas Gadjah Mada, 2004)
This paper investigates the ability of microorganisms in a biofilm to degrade polychlorinated biphenyls (PCBs) using a three-phase fluidized bed aerobic biofilm reactor. Water was spiked with PCBs that contain mainly Aroclor 1260 to simulate PCB-contaminated water. The